District thermal systems: State of the art and promising evolutive scenarios. A focus on Italy and Switzerland. (February 2021) - Caputo, Paola; Ferla, Giulio; Belliardi, Marco; Cereghetti, Nerio
Highlights: District thermal systems (DTS), promising for 2030 and 2050 goals, are investigated. A review of the technical literature concerning different classifications of DTS is presented. European DTS are analysed, with particular insights on Italian and Swiss operative context. 5th generation DTS are investigated, with insights on Italian and Swiss examples. Technological features of DTS and their possible evolutive scenarios are discussed. Abstract: In the framework of the built environment enhancement towards energy strategy 2050, interesting debates have been developed at building and district scale. In relation to thermal energy end-uses, that are the most impacting in buildings, district thermal systems (DTS) offer a great flexibility in terms of heat generation technologies and renewable resources integration, resulting, in case of proper management and supply conditions, in primary energy and greenhouse gases savings compared to the most diffuse technologies operating at building scale. Recent progresses in DTS have followed over the years the development of technologies and energy policies resulting in different configurations and operative schemes. The present contribution reviews the different classifications of DTS provided in the technical literature. The European framework of DTS is then analysed, with particular insights to the Italian and Swiss operative context. Currently, DTS have a marginal role in these two countries and can mainly be classified as high-temperature or mid-generation systems. However, there are also innovative systems, on which the attention of the involved stakeholders is focusing. The technological features of DTS are discussed, in order to provide possible challenging evolutive scenarios to enhance their performance and economic appeal through the evaluation of successful recent examples.